Short-course Regimens of Liposomal Amphotericin B for the Treatment of Mediterranean Visceral Leishmaniasis in Children: An 11-year Retrospective Study at a Tertiary Care Center. Issue 9 (September 2017) - Krepis, Panagiotis; Argyri, Ioanna; Krepi, Adamantia; Syrmou, Areti; Spyridis, Nikos; Tsolia, Maria
Abstract : Background: Visceral leishmaniasis (VL) remains an important public health problem in endemic regions. Current antileishmanial agents share several limitations including potentially serious side effects and the risk of clinical failure. Objectives: Aim of this study was to examine the effectiveness and safety of short-course liposomal amphotericin B (L-AmB) regimens in the treatment of childhood VL in our area. Methods: The cases of 43 VL patients (20 males; 23 females; mean age: 4.6 years) treated at a tertiary children's hospital over an 11-year period were retrospectively reviewed. Diagnosis was confirmed with identification of Leishmania spp. in bone marrow samples and/or a positive serologic test. All patients were treated with 5 different L-AmB regimens at a dose of 18–22 mg/kg. Results: Initial response to treatment was attained in all patients (100%), while definitive cure at 6 months was achieved in 98% of patients. Adverse effects were recorded in 14 children and consisted mostly of infusion reactions and electrolyte disorders. Self-limiting nephrotoxicity was observed in 3 patients including a 12-year-old girl in whom acute kidney injury was developed. In addition, ventricular arrhythmias developed in a 13-year-old boy necessitating drug discontinuation. Although side effects were more frequent with the 2-day regimen, the difference with regard to toxicity between dosing regimens was not significant. Conclusions: Short-course L-AmB regimens are effective and safe for the treatment of childhood VL in our area. Our findings suggest that large L-AmB doses can possibly account for a higher rate of adverse events including nephrotoxicity.